Upgrading of Philippine coals with emphasis on the application of the oil agglomeration technology - Herrera, Alice B.
Coal has the advantage of being an abundant energy resource in the Philippines. However, the uncontrolled utilization of coal, particularly low grade coal, using existing conventional technologies could have adverse effects on the environment on a local, regional and global scale. These adverse environmental effects of coal use, if not properly addressed, could hamper expanded coal utilization in the Philippines which is in line with the government's thrust on sustainable development. Aside from this, the Philippines is becoming more and more concern with its environment jut like the rest of the world. One of the promising techniques for handling very fine coal and recovering most of the carbonaceous material is called "oil agglomeration". Aside from being an efficient and effective technique to selectively separate coal from mineral matter and beneficiate the coal to a higher grade, oil agglomeration produces agglomerates which have a very good storage and handling properties and have low and consistent level of impurities.
The main objective of the research work is to determine whether the oil agglomeration process is an effective technique for lowering the ash content of Philippine coal fines and for recovering most of the combustible carbonaceous material. The study involved the process optimization varying oil dosage, pulp density, and agglomeration period and determining their effects on percentage recovery of clean agglomerates and percentage ash removal. It also involved modeling of the recovery and ash removal phenomena. The recovery of carbonaceous materials ranged from 67 to 92% while the percentage ash removal ranged from 16 to 62%. Process variables such as pulp density, the amount of agglomerating oil and the agglomeration period affect significantly the recovery of clean agglomerates and the percentage ash removal. High percentage recovery of agglomerates of about 89.36% and high percentage ash removal of 41% can be obtained when using the optimum values of 21.11 to 23.78% oil dosage, 22.09% pulp density at an agglomeration period of 3 minutes.
Thesis (Ph.D. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Coal -- Carbonization. -- Philippines; Agglomeration; Coal gasification -- Philippines; Coal -- Environmental aspects -- Philippines